2023
DOI: 10.3390/membranes13100840
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Bioactive Nanofibrous Materials Combining Medicinal and Aromatic Plant Extracts and Electrospinning Method

Nikoleta Stoyanova,
Nasko Nachev,
Mariya Spasova

Abstract: Since antiquity, humans have known about plants as a medicinal cure. Recently, plant extracts are attracting more attention as a result of their natural origin and wide range of desirable features. Nanotechnology’s progress and innovations enable the production of novel materials with enhanced properties for a broad range of applications. Electrospinning is a cutting-edge, flexible and economical technique that allows the creation of continuous nano- and microfibrous membranes with tunable structure, character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“…According to the results of previous studies, H. perforatum oil or solvent-based extracts have antibacterial and anti-biofilm properties against the common bacteria associated with periodontitis, such as P. gingivalis , Escherichia coli , S. mutans , S. sobrinus , and S. aureus Furthermore, Bagheri et al showed that H. perforatum oil has the same bactericidal ability as that shown by the antibiotic control groups [ 88 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of previous studies, H. perforatum oil or solvent-based extracts have antibacterial and anti-biofilm properties against the common bacteria associated with periodontitis, such as P. gingivalis , Escherichia coli , S. mutans , S. sobrinus , and S. aureus Furthermore, Bagheri et al showed that H. perforatum oil has the same bactericidal ability as that shown by the antibiotic control groups [ 88 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poly(lactic acid) (PLA) [21], poly(vinyl alcohol) (PVA) [16,22], polyvinylpyrrolidone (PVP) [23][24][25], polyurethane (PU) [26], polyethylene glycol (PEG) [27], polycaprolactone (PCL) [28], polyethylene oxide (PEO), polylactic acid (PLGA), polystyrene (PS) and polyglycerol (PG), chitosan (CS), gelatin, pectin, collagen [18] are widely used in ES in the literature.…”
Section: Electrospinningmentioning
confidence: 99%
“…Plants have been used for therapeutic purposes since ancient times. However, due to their natural structure and many useful and effective properties, plant extracts have gained more popularity in recent years [27]. According to the World Health Organization, there are approximately 20,000 medicinal plants in 91 countries.…”
Section: Plant and Plant Extractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of electrospun fibers for wound dressing applications, containing natural bioactive substances, represents a relatively recent technological advancement. Several research studies published over the past five years on this topic highlight the versatility of electrospun materials for diverse therapeutic applications, in addition to tailorable chemical and physical properties [ 14 , 15 , 16 , 17 , 18 , 19 ]. Our methodology adopts the manufacturing protocols developed by Nanofaber srl to produce oily extract-loaded electrospun membranes for wound healing applications.…”
Section: Introductionmentioning
confidence: 99%